On the edge - Cross, Gillian (Oxford University, 2000)
When Tug wakes up, he is not in his own bedroom at home. The door is locked and there are bars across the window. Loud music hammers through the house and through his head. Then a woman comes in and says that she is his mother, but Tug knows that she is not his mother . . . Outside, Jinny stares through the trees at the lonely house on the hill. She hears strange noises, but she turns away. After all, it's none of her business